Alcohol Extracts From Ganoderma lucidum Delay the Progress of Alzheimer’s Disease by Regulating DNA Methylation in Rodents - Lai, Guoxiao; Guo, Yinrui; Chen, Diling; Tang, Xiaocui; Shuai, Ou; Yong, Tianqiao; Wang, Dongdong; Xiao, Chun; Zhou, Gailian; Xie, Yizhen; Yang, Burton B.; Wu, Qingping (Frontiers in Pharmacology, 2019)
Age-related changes in methylation are involved in the occurrence and development of tumors, autoimmune disease, and nervous system disorders, including Alzheimer’s disease (AD), in elderly individuals; hence, modulation of these methylation changes may be an effective strategy to delay the progression of AD pathology. In this study, the AD model rats were used to screen the main active fractions from the mushroom, Ganoderma lucidum, for anti-aging properties, and their effects on DNA methylation evaluated. The results of evaluation of rats treated with 100 mg/kg/d of D-galactose to induce accelerated aging showed that alcohol extracts of G. lucidum contained the main active anti-aging fraction. The effects on DNA methylation of these G. lucidum extracts were then evaluated using SAMP8 and APP/PS1 AD model mice by whole genome bisulfite sequencing. Molecular docking analysis was carried out to screen for molecules regulated by specific components, including ganoderic acid Mk, ganoderic acid C6, and lucidone A, which may be active ingredients of G. lucidum, including the methylation regulators of Histone H3, MYT, DNMT3A, and DNMT3B. Auxiliary tests also demonstrated that G. lucidum alcohol extracts could improve learning and memory function, ameliorate neuronal apoptosis and brain atrophy, and down-regulate the expression of the AD intracellular marker, Aβ1–42. We concluded that alcohol extracts from G. lucidum, including ganoderic acid and lucidone A, are the main fractions involved in delaying AD progression.